Students’ Perception of the Implementation Picture Series in Writing Classroom - Anfa Farkhan Al Faya (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Most of the students have difficulties in writing. They had poor ability to arrange sentences in correct logical order and good paragraph structure. However, the previous studies showed that the problems of writing are not only based on the inability of the students to write, but also by the inappropriate method used by the teacher in the learning process. Most teachers do not know about what kind of best visual aid that can be applied to develop the learners’ ability in writing class. This research is looking at teacher’s and students’ perceptions of the implementation picture series in the writing classroom. For collecting the data, the researcher used questionnaires and interviews. All of the participants were third-grade students in SMP Negeri 1 Sumberlawang, in the Academic year 2019/2020. The researcher involved 16 students at eleventh-grade junior high school. This study is expected that the implementation of using picture series as a media in the learning process can be beneficial for teachers and students, such as improving the learners’ writing ability, improving students’ participation in the learning process, fun learning environment, and improving students’ writing interest.